ENVIRONMENTAL LAW AND SOCIAL JUSTICE IN ACHIEVING SDG 11: A STUDY OF BANDAR LAMPUNG CITY: HUKUM LINGKUNGAN DAN KEADILAN SOSIAL DALAM CAPAIAN SDG 11: STUDI KOTA BANDAR LAMPUNG - Ainita, Okta; Nuzir, Fritz Akhmad; Ardiansyah, Muhammad; Rahmawati, Aulia (Pusat Studi Konstitusi dan Perundang-undangan, 2025)
Sustainable urban development is the main agenda in Sustainable Development Goals (SDG) 11, which demands inclusive, safe, resilient, and sustainable cities. However, there is still a gap between normative environmental law regulations and practices in the field, especially related to the deficit of green open space, the existence of slums, and the lack of public participation. This study aims to analyze the integration of the Pancasila social justice principle into environmental law to strengthen the implementation of SDG 11, focusing on the City of Bandar Lampung as a case study. The research methodology used is normative and empirical legal research with qualitative-descriptive analysis techniques, through a study of laws and regulations and field data related to spatial planning, green open spaces, and slums. The results show that although Indonesia's legal framework guarantees the right to a good environment, implementation at the local level does not yet reflect the principles of social justice. This is reflected in the RTH deficit of only around 10% (national standard of 30%), the existence of slums ±60.01 ha in Panjang District, and 1,115 units of uninhabitable houses, which show spatial injustice and weak protection for marginalized groups. The results of the study can be concluded that the integration of Pancasila social justice values through collaborative governance based on multi-stakeholder partnership is an important strategy to strengthen the achievement of SDG 11. Theoretically, this study expands the study of environmental law based on social justice, while practically providing inclusive, participatory, and equitable policy recommendations for sustainable urban development in Indonesia.